Pedagogical Characteristics of Education of Love for Nature in Preschool Children. (Texas Journal of Philology, Culture and History, 2022)
This article provides information on how to instill a love of nature in preschoolers, that soil, water, air, flora and fauna, underground and terrestrial resources are created for human needs